Antioxidant activity of ethanolic extract of three Selaginella species from Java Island, Indonesia - M Miftahudin; Rini Hasibuan; Tatik Chikmawati (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Miftahudin, Hasibuan RS, Chikmawati T. 2019. Antioxidant activity of ethanolic extract of three Selaginella species from Java Island, Indonesia. Biodiversitas 20: 3715-3722. Three Selaginella species, S. ornata, S. plana, and S. willdenowii, from Java Island, Indonesia, have been known to have antioxidant properties; however, in vivo antioxidant activities of these species have not been reported. This research aimed to evaluate the in vivo antioxidant activity of ethanolic extract of three Selaginella species. The 70% ethanol extract of three Selaginella species at four different doses was administered to mice one day before being treated with oxidative stress. The liver tissue of mice treated with or without oxidative stress was analyzed their lipid peroxidation by measuring MDA concentration and Superoxide Dismutase (SOD) activities. The results showed that there were variations in antioxidant activity among the three Selaginella species. In general, the dose of 0.3 g extract kg-1 BW has been able to reduce lipid peroxidation and increase SOD activity. The administration of S. ornata extract to the mice at 1.2 g extract kg-1 BW reduced the MDA concentration to the lowest level, but the same dose of two other Selaginella extracts caused toxic effects in mice. The antioxidant activities of S. ornata and S. plana were better than that of S. willdenowii extract, and among those species, S. ornata has the best antioxidant activity.